KARAKTERSITIK FISIKOKIMIA EKSTRAK BEKATUL BERAS HITAM ASAL DESA CENGOLO - TABANAN SEBAGAI SUMBER PEWARNA FUNGSIONAL - Widnyani, Ida Ayu Putu Ary; Wartini, Ni Made; Wrasiati, Ni Luh Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 10 No 2 (2023): Scientific Journal of Food Technology (September)DO - 10.24843/MITP.2023.v10.i02.p68-74, 2024)
Black rice bran is a byproduct of the black rice removal process which has the potential to become a functional food colorant. This research aims to Determine the effect of materials comparison with solvent and pH solvent to the characteristic of extract from rice black bran and  determine the material ratio with solvent and pH solvent to produce the best black rice bran extract that can be applied to food products. This study used a randomized block design (RAK) 2 factor 3 groups. The extraction process used the maseration method. The results showed that the comparative treatment of the material with solvent and pH and the interactions affected the rendement parameter, anthocyanin content, and colors (L*, a*, and b*). The result showed the best treatment is the comparative treatment with solvent 1:10 and pH 1 is the best treatment. The characteristic is rendemens 0,0089%, total anthocyanin 596,944 mg/l, L* value 51.533 a* value 26.933 b* value 32.133.